Application of atmospheric pressure field desorption for the analysis of anionic surfactants in commercial detergents - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2023)
Recent work has shown that field desorption (FD) and field ionization (FI) using activated field emitters may be performed at atmospheric pressure, too. While some limitations apply to atmospheric pressure field desorption (APFD) mass spectrometry (MS), the method can deliver both positive and negative even electron ions of highly polar or ionic compounds. Furthermore, APFD even permits the generation of positive molecular ions of polycyclic aromatic compounds. Here, an application of negative-ion APFD for the analysis of anionic surfactants contained in commercial detergent products for body care, household, and technical uses is presented. The samples include liquid soaps and shower gels, dishwashing liquids, and cooling lubricants. Surfactant solutions in methanol/water or pure methanol at 2-10 µl ml−1 were deposited on commercial 13-µm activated tungsten emitters. The emitters were positioned in front of the atmospheric pressure interface of a Fourier transform-ion cyclotron resonance (FT-ICR) mass spectrometer by means of a slightly modified nano-electrospray ionization (nanoESI) source. The entrance electrode of the interface was set to positive high voltage with respect to the emitter at ground potential. Under these conditions, negative-ion desorption was achieved. The surfactant anions, organic sulfates and organic sulfonates, were characterized by accurate mass-based formula assignments, and in part, by tandem mass spectrometry. The negative-ion APFD spectra were compared to results by negative-ion electrospray ionization (ESI) either obtained using the FT-ICR mass spectrometer or by using a trapped ion mobility-quadrupole-time-of-flight (TIMS-Q-TOF) instrument when product ions of low m/z needed to be detected in tandem MS.
Im Web of Science ist der DOI fälschlich als 10.1007/s00216-023-04917 angegeben
Gesehen am 19.10.2023